A Review On Bioremediation Of Petroleum Hydrocarbon Contaminants In Soil - Thapa, Bijay; KC, Ajay Kumar; Ghimire, Anish (Kathmandu University Journal of Science, Engineering and Technology, 2012)
This review article illustrates the pros and cons of using bioremediation process for the remediation of petroleum contaminants in soil. Bioremediation along with other processes have been used to remediate petroleum hydrocarbon contaminants in soil in past. The major constituents of most crude oils are biodegradable, so bioremediation has proven to be cheap and efficient than others techniques. Different organisms are employed using various technique of bioremediation according to hydrocarbon present in the contaminated soil. Bioremediation is simpler, less labor intensive and public attitude toward bioremediation are generally favorable, the lack of knowledge about microorganisms and their natural role in the environment could affect the acceptability of their use. However, bioremediation can be considered one of the best technologies to deal with petroleum product contaminated soil. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6056 KUSET 2012; 8(1): 164-170